2015
DOI: 10.4236/ijcns.2015.85013
|View full text |Cite
|
Sign up to set email alerts
|

Compression of ECG Signal Based on Compressive Sensing and the Extraction of Significant Features

Abstract: Diagnoses of heart diseases can be done effectively on long term recordings of ECG signals that preserve the signals' morphologies. In these cases, the volume of the ECG data produced by the monitoring systems grows significantly. To make the mobile healthcare possible, the need for efficient ECG signal compression algorithms to store and/or transmit the signal efficiently has been rising exponentially. Currently, ECG signal is acquired at Nyquist rate or higher, thus introducing redundancies between adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…As we aim to reconstruct the data with minimum measurements it is found meaningless for going CR above of 60%. The wavelets are decomposed at level 4 as in [18]. Ratios for the MIT data 101m, Table.3 indicate the same for 101m.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we aim to reconstruct the data with minimum measurements it is found meaningless for going CR above of 60%. The wavelets are decomposed at level 4 as in [18]. Ratios for the MIT data 101m, Table.3 indicate the same for 101m.…”
Section: Resultsmentioning
confidence: 99%
“…There are lots of papers published in the field of CS based ECG reconstruction most of them considers CS as a technique for compression rather than a sensing paradigm [12][13][14][15][16][17]. Recently in May-2015 Abo-Zahhad, et.al published their work [18] which is showing some promising results, In that they have estimated the QRS complex from the available data and subtracted it from the original and CS techniques are applied on the error signal. The major drawback here is that prior information of the data has to known before, and thresholding has also been employed to increase sparsity.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on improving the ECG signal sparsity using QRS-complex estimation based on the peaks and locations of Q, R and S waves. Then, the estimated QRS-complex is subtracted from the original ECG signal and the resulting differential signal is manipulated using CS technique as shown in Figure (3) where fewer measurements are determined from the resulting error signal [21][22]…”
Section: Compression Of Ecg Signal Based On Cs and The Extraction Of mentioning
confidence: 99%
“…This limits the rank of the sensing matrix required for preserving the Restricted Isometry Property (RIP), leading to limited compression ratio (CR). On the other hand, conventional CS frameworks [7,8,5] that adopt predetermined basis for reconstruction underestimate the intricacy of philological signals and overlook the criticality of individual variability to signal fidelity, which results in very limited reconstruction performance especially at high CR [6]. Our previous study [9] has shown that learned dictionaries can better approximate the underlying statistical model of input data.…”
Section: Introductionmentioning
confidence: 99%